2022
DOI: 10.15252/embr.202154271
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelial‐immune crosstalk contributes to vasculopathy in nonalcoholic fatty liver disease

Abstract: The top cause of mortality in patients with nonalcoholic fatty liver disease (NAFLD) is cardiovascular complications. However, mechanisms of NAFLD‐associated vasculopathy remain understudied. Here, we show that blood outgrowth endothelial cells (BOECs) from NAFLD subjects exhibit global transcriptional upregulation of chemokines and human leukocyte antigens. In mouse models of diet‐induced NAFLD, we confirm heightened endothelial expressions of CXCL12 in the aortas and the liver vasculatures, and increased ret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…These abnormal immune responses are predominantly orchestrated by CD4 + helper T cells, which are highly activated throughout the early and advanced NASH stages in the LIDPAD model. This corroborates findings that T-lymphocytes are heavily involved in NAFLD deterioration( 3840 ). A recent study also identified an integral role of activated CD4 + T cells at fibrotic sites in NASH-driven hepatic inflammation and fibrosis( 41 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These abnormal immune responses are predominantly orchestrated by CD4 + helper T cells, which are highly activated throughout the early and advanced NASH stages in the LIDPAD model. This corroborates findings that T-lymphocytes are heavily involved in NAFLD deterioration( 3840 ). A recent study also identified an integral role of activated CD4 + T cells at fibrotic sites in NASH-driven hepatic inflammation and fibrosis( 41 ).…”
Section: Discussionsupporting
confidence: 91%
“…This model supports a liver-pancreas axis that promotes compensatory pancreatic islet cell hyperplasia, a phenomenon similarly observed in animal models of insulin resistance( 35 ) and in humans, where there is a clear correlation between BMI and β-cell mass( 36 ) and thereafter fatty liver and the development of type-2 diabetes( 37 ). Furthermore, LIDPAD mice also displayed NAFLD-associated vasculopathy, with heightened endothelial expression of CXCL12 in the aortas and the liver vasculature( 38 ). These various metabolic dysfunctions and extrahepatic comorbidities are collectively absent in current NAFLD models.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that Treg disorder is attributed to the development of MAFLD‐associated HCC (MAFLD‐HCC) from MAFLD. The clinical data showed that patients with moderate MAFLD‐HCC had a higher level of Treg cells to suppress host antitumor immunity and dramatically facilitate the initiation and progression of cancer [ 98 ]. Butyrate, a metabolite of gut microbiota from MAFLD‐HCC patients, led to Treg cells amplification meanwhile reduced CD8 + T cells and B cells quantity via enhancing Foxp3 expression and restraining proinflammatory cytokines to reinforce immunosuppressive response of peripheral blood mononuclear cells (PBMC) from non‐MAFLD individuals [ 98 ].…”
Section: T Cells and Mafldmentioning
confidence: 99%
“…Nonetheless, we demonstrated that mQTLs identified in other studies 16,17 , including those identified in a cross-ancestry analysis 17 , were well replicated in our database. We captured whole blood-based DNA methylation profiles, which can serve as candidate biomarkers for diseases; however, they may not reflect tissue-specific 35 . MR analysis was used to showcase the potential application of our mQTL database; however, MR analysis is based on assumptions that may not be testable 36 .…”
Section: Mendelian Randomization Analysismentioning
confidence: 99%